0652 Associations Between Anhedonia and Maladaptive Beliefs About Sleep in Middle Age and Older Adults with Insomnia Disorder. (25th May 2022) - Tully, Isabelle; Tutek, Joshua; Gumport, Nicole; Simpson, Norah; Dietch, Jessee; Palaniappan, Latha; Manber, Rachel
Abstract: Introduction: Comorbid depression often exacerbates dysfunctional beliefs about sleep in those with insomnia disorder. Anhedonia, a core symptom of depression, may be mechanistic in this association. Previous research suggests that, when appraising potential decisions, individuals with anhedonia regularly overestimate the probability of negatively valenced outcomes and underestimate the likelihood of positive outcomes. This study explores the relationship between anhedonia and sleep-related cognitions in patients with insomnia disorder. Methods: Adults 50 years and older (N = 241) who met DSM-5 criteria for insomnia disorder were enrolled in a randomized controlled trial assessing the effectiveness of a stepped care approach to delivering Cognitive Behavioral Therapy for Insomnia. At baseline, participants completed the Dysfunctional Beliefs and Attitudes about Sleep Scale, Pre-Sleep Arousal Scale (cognitive subscale), Beliefs about Medications Questionnaire (Subscales assess the belief that hypnotics are necessary and concern regarding consequences of use), and PROMIS sleep-related impairment short form. A t-test was used to compare participants who did and did not endorse anhedonia on the Geriatric Depression Scale (GDS). We also correlated the Patient Health Questionnaire-4 (PHQ-4) anhedonia item with sleep-related cognition measures. Results: Participants reporting anhedonia (GDS) endorsed greater dysfunctional beliefs about sleep (p < .001, d = 0.44) and sleep-related impairment (p < .01, d = 0.39). Groups did not differ significantly regarding belief in the necessity of sleep medications and concern with hypnotic use, nor in pre-sleep arousal. Higher anhedonia (PHQ-4) was correlated with more severe dysfunctional beliefs about sleep (r = .20, p < .01), belief in the necessity of hypnotics to manage sleep disturbance (r = .22, p < .001), and greater pre-sleep arousal (r = .18, p < .01). Conclusion: Endorsement of anhedonia was associated with stronger dysfunctional beliefs about sleep in this sample of middle age and older adults with insomnia disorder. Participants reporting anhedonia also reported greater sleep-related impairment. Exploring anhedonia as a transdiagnostic symptom that influences interpretation of sleep-related difficulties may elucidate underlying mechanisms that sustain maladaptive cognitions. Prospective, multi-method studies will be essential to clarify predictive interactions between reward system dysfunction and sleep-related beliefs in those with insomnia disorder. Support (If Any): 1R01AG057500